AIr transportation in Nigeria : Strategies for 21st Century - Charles, Diepiriye David; Okereke-Onyiuke, Ndi (Lagos Ton-Priye Integrated Resources, 1997)
This book is expected to find its rightful place in aviation, business, transport and management education. Scholars of aviation and industry players will find the volume useful and of immense value both in the class room and in the field.
Includes bibliographical references and index
rpm 16/08/16
Loans
Keywords: Air transportation; Air transportation industry; Air transportation policy